1982
DOI: 10.1128/iai.37.2.710-719.1982
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated cytotoxicity against rat fibroblasts induced by Actinomyces viscosus

Abstract: Cell-mediated cytotoxicity against syngeneic fetal rat fibroblasts that require in vitro exposure of effector cells to Actinomyces viscosus Nyl fractions was investigated by measuring the uptake of radioactivity by fibroblasts during a 2-h pulse with [14C]aminoisobutyric acid after 1 to 3 days of coculture with splenic effector cells. By using splenocytes from inbred RIC-Sprague-Dawley rats as effector cells and syngeneic embryonic rat fibroblasts as target cells, strong cellmediated cytotoxicity dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…viscosus did not exceed lo%, even at an effector to target ratio of 1O:l. This makes it unlikely that the 96% suppression caused by the peritoneal exudate cells was due to the lymphocytes they contained. The small suppressive effect caused by splenic lymphocytes was comparable to that observed by Gaegauf-Zollinger et al (1982) at a similar effector to target ratio, when no A . viscosus preparation was added in vitro.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…viscosus did not exceed lo%, even at an effector to target ratio of 1O:l. This makes it unlikely that the 96% suppression caused by the peritoneal exudate cells was due to the lymphocytes they contained. The small suppressive effect caused by splenic lymphocytes was comparable to that observed by Gaegauf-Zollinger et al (1982) at a similar effector to target ratio, when no A . viscosus preparation was added in vitro.…”
Section: Discussionsupporting
confidence: 62%
“…Further studies are in progress in this direction. Gaegauf-Zollinger et al (1982) have demonstrated suppressive or cytotoxic effects on fibroblasts by lymphocytes exposed in vitro to an A. viscosus preparation. This raised the possibility that lymphocytes contained in the peritoneal exudate cells (up to 7%) were the cause of the suppressive effect of this cell population.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were grown in Dulbecco minimal essential medium supplemented with 10% heat-inactivated newborn bovine serum (GIBCO Europe), 15 p.g of 8-azaguanine per ml, 2 mM glutamine, 100 IU of penicillin per ml, and 100 ,ug of streptomycin per ml. The isolation and cultivation of diploid fetal rat fibroblasts have been described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Extracts of A. viscosus have even been shown to be cytotoxic to rat embryo fibroblasts (5). A recent report of Larava et al (8) describes fibroblast inhibitory factors that seem to be endotoxin extracted from whole dental plaque.…”
Section: Infect Immunmentioning
confidence: 99%